Optical Coherence Tomography-Guided Transepithelial Phototherapeutic Keratectomy for Central Corneal Opacity in the Pediatric Population - Sloan W. Rush; Ryan B. Rush (Journal of Ophthalmology)
Purpose. To report the outcomes of optical coherence tomography- (OCT-) guided transepithelial phototherapeutic keratectomy (PTK) for central corneal opacity in the pediatric population. Methods. The charts of 10 eyes of 8 children aged 9 to 17 with central corneal opacity from various pathologies who underwent a standardized OCT-guided transepithelial PTK technique at a single private practice institution were retrospectively reviewed. The corneal topographic findings, OCT measurements, and visual results with refractive outcomes were analyzed 6 months after the PTK treatment. Results. All 10 eyes tolerated the procedure well without any significant intraoperative or postoperative complications. Uncorrected and best spectacle-corrected visual acuity (BSCVA) significantly improved postoperatively (p<0.0001 and p=0.0045, respectively). The absolute value of spherical equivalent on cycloplegic refraction significantly improved postoperatively as well (p=0.0014), but there were no significant changes in topographic measurements. Seven out of the 10 eyes had complete resolution of the central corneal opacity on OCT imaging. None of the subjects lost any lines of BSCVA and developed recurrence of the corneal opacity from the primary disease condition or required keratoplasty during the follow-up period. Conclusions. OCT-guided transepithelial PTK can provide excellent visual outcomes in pediatric patients with central corneal opacities.